Globalisation, cultural diversity and Lusophony: trans-spatial circulation of Portuguese speech and its relationship with other speeches - Lopes, Armando Jorge (2018)
I shall discuss several questions involving the concepts of globalisation, cultural diversity and lusophony in a transdisciplinary fashion, resorting to the notions of crossings and passages, mediated by Applied Linguistics and supported by Language Planning and Language Policy. The crossing, wrapped in novelty and perilousness, speaks of oceans, affording us complex challenges and, at times, frightening us. The passage seems to be more controlled, and associated with less enigmatic and more secure experiences, perhaps because both banks of a river can usually be seen from any point as we pass through it. In a river, we travel across from one bank to the other. And in the ocean, what happens? Lusophony and its contextualisation, in my opinion, is the crossing, viewed from a transdisciplinary perspective and through applied linguistics, including cultural diversity in a world claimed as global. Through Language Planning and Language Policy, both established as useful tools for a possible outline of some futuristic notion, Lusophony is here understood as passage. The focus of the present article falls therefore upon the concept of Lusophony as a place of reflection, of knowledge as well as recognition of oneself and the Other. This concept of Lusophony is instantiated by the notion of relation vis-à-vis globalisation and by the essence here portrayed by the linguistic ecological system of Portuguese.